Enhancing Public Service Quality in Tejamulya Village: Challenges and Opportunities - Jarkasih, Aceng (Papanda Publishier, 2024)
This research aims to assess the quality of public services at the Tejamulya Village Government Office in Argapura District, Majalengka Regency. Employing a descriptive qualitative method, the study portrays or describes the condition of the examined object as it exists. Data collection techniques utilized in this research involved observation, interviews, and documentation. The informants in this study consisted of eight individuals, comprising three village government officials and five members of the community. The focus of this research is on the quality of public services at the Tejamulya Village Government Office in Argapura District, Majalengka Regency, assessed through Zeithaml's theory comprising five measurement indicators: tangibility, reliability, responsiveness, assurance, and empathy. The research findings revealed several indicators that were not adequately fulfilled, including incomplete and uncomfortable facilities at the service office for the community, slow and unresponsive service delivery from staff, inconsistent timeliness in service, a lack of time assurance for services, and staff members demonstrating impolite behavior when serving the public. This study contributes to providing a comprehensive overview of the challenges and opportunities to enhance the quality of public services at the Tejamulya Village Government Office.